Intraosseous Ganglion Cysts of the Carpus: Current Practice. (December 2015) - Osagie, Liza; Gallivan, Samantha; Wickham, Neil; Umarji, Shamim
Intraosseous cysts of the carpal bones are an infrequent cause of chronic wrist pain. The main body of work has investigated their occurrence in the proximal carpus, with limited incidence in the distal row. We review the current literature on the treatment of symptomatic carpal cysts following the report of a 17-year-old male with a 12-month history of progressive right wrist pain due to an intraosseous ganglion of the trapezoid. This review explores the pathology of carpal cysts, their varying presentation and current treatments.